Clinical Determinants of Dual Tasking in People With Premanifest Huntington Disease. Issue 4 (22nd January 2021) - Reyes, Alvaro; Bartlett, Danielle M; Rankin, Timothy J; Zaenker, Pauline; Turner, Kate; Teo, Wei-Peng; Fu, Shih Ching; Domingos, Josefa; Georgiou-Karistianis, Nellie; Ziman, Mel; Cruickshank, Travis M
Abstract: Objective: Dual-tasking deficiencies are common in people with Huntington disease (HD) and contribute to reduced functional independence. To date, few studies have investigated the determinants of dual-tasking deficiencies in this population. The reliability of dual-tasking measures has also been poorly investigated in HD. The purpose of this study was to investigate the influence of clinical determinants on dual-tasking performance and to determine the association of disease burden outcomes on dual-tasking performance in individuals with premanifest HD. Methods: Thirty-six individuals with premanifest HD and 28 age- and sex-matched healthy controls were recruited for this study. Participants performed 3 single-task (2 cognitive and 1 motor) and 2 dual-task assessments, comprising motor (postural stability) and cognitive (simple or complex mental arithmetic) components. In addition, participants performed a comprehensive clinical battery comprising motor, cognitive, mood, and sleep assessments as well as lifestyle and disease burden measures. Results: Poorer sleep quality was associated with greater cognitive dual-task cost in individuals with premanifest HD. Compared with healthy controls, people with premanifest HD demonstrated an impaired capacity to dual task. Dual-task measures exhibited acceptable test–retest reliability in premanifest HD and healthy control groups. Conclusion: These results show that dual-tasking measures are sensitive and reliable in individuals with premanifest HD. Furthermore, poor sleep quality is associated with worse cognitive performance on dual tasks, which should be considered by rehabilitation specialists when examining and therapeutically managing dual-tasking problems in individuals with HD and other neurodegenerative populations in the future. Impact: This study adds important knowledge to the sparse literature on dual-tasking deficiencies in people with HD. When examining and therapeutically managing dual-tasking problems in this and other neurodegenerative populations, rehabilitation specialists should consider that people with premanifest HD may have an impaired capacity to dual task. Clinicians also should assess sleep quality, as poorer sleep quality is associated with worse cognitive performance on dual tasks in these individuals. Lay Summary: If you have premanifest HD and poor quality of sleep, you may pay more attention to maintaining postural stability rather than performing arithmetic calculations to reduce the risk of falling.